Arginine does not rescue p.Q188R mutation deleterious effect in classic galactosemia - Haskovic, M; Derks, B; Van Der Ploeg, L; Trommelen, J; Nyakayiru, J; Van Loon, L; Mackinnon, S; Yue, W; Peake, R; Zha, L; Demirbas, D; Qi, W; et al. (BioMed Central, 2018)
Background Classic galactosemia is a rare genetic metabolic disease with an unmet treatment need. Current standard of care fails to prevent chronically-debilitating brain and gonadal complications. Many mutations in the GALT gene responsible for classic galactosemia have been described to give rise to variants with conformational abnormalities. This pathogenic mechanism is highly amenable to a therapeutic strategy based on chemical/pharmacological chaperones. Arginine, a chemical chaperone, has shown beneficial effect in other inherited metabolic disorders, as well as in a prokaryotic model of classic galactosemia. The p.Q188R mutation presents a high prevalence in the Caucasian population, making it a very clinically relevant mutation. This mutation gives rise to a protein with lower conformational stability and lower catalytic activity. The aim of this study is to assess the potential therapeutic role of arginine for this mutation. Methods Arginine aspartate administration to four patients with the p.Q188R/p.Q188R mutation, in vitro studies with three fibroblast cell lines derived from classic galactosemia patients as well as recombinant protein experiments were used to evaluate the effect of arginine in galactose metabolism. This study has been registered at https://clinicaltrials.gov (NCT03580122) on 09 July 2018. Retrospectively registered. Results Following a month of arginine administration, patients did not show a significant improvement of whole-body galactose oxidative capacity (p = 0.22), erythrocyte GALT activity (p = 0.87), urinary galactose (p = 0.52) and urinary galactitol levels (p =0.41). Patients’ fibroblasts exposed to arginine did not show changes in GALT activity. Thermal shift analysis of recombinant p.Q188R GALT protein in the presence of arginine did not exhibit a positive effect. Conclusions This short pilot study in four patients homozygous for the p.Q188R/p.Q188R mutation reveals that arginine has no potential therapeutic role for galactosemia patients homozygous for the p.Q188R mutation.